ANALISIS KRITIS TERHADAP PEMBANGUNAN DUNIA KETIGA DAN TRANSFORMASI AGRARIA DI INDONESIA - Nur Utaminingsih (Departemen Ilmu Hubungan Internasional Univesitas Hasanuddin, 2019)
This article discusses a critical investigation of the topic of Third World development and the issue of agrarian transformation in Indonesia. This study uses a qualitative methodology with an in-depth interpretation tracing model of each research component. The Capitalist Block's power / knowledge has been successfully distributed locally in Third World Countries through the Development Project. The local distribution of power / knowledge through the mechanism of creating abnormalities and the formation of the development apparatus plays a role in translating the basic values ​​of capitalism in Indonesia. Agrarian transformation has become one of the social realities of the successful existence of capitalism in the development of Indonesia as a third world country. The meaning of Indonesia as an agrarian country towards agrarian (earth, water, sea, space, and human society, as regulated in UUPA 1960) is increasingly result-oriented through industrialization and commercialization. Agrarian economy morals in Indonesia prioritize control, ownership and use of